First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Tohiran, Kamil; Nasir, Dzulhelmi Muhammad; Burhanuddin, Maisarah; Nobilly, Frisco; Zulkifli, Raja; Moslim, Ramle; Yahya, Muhammad Syafiq; Norhisham, Ahmad Razi; Lechner, Alex M.; Md Sharif, Badrul Azhar (Springer Nature, 2024)
Long-term use of agrochemicals in the oil palm plantation sector, particularly chemical pesticides for pest control, can have a negative impact on the environment. The use of biological control has long been advocated as an alternative to pesticides, but empirical evidence in the context of oil palm plantations is very limited. This study aims to assess whether the installation of artificial bird perches can attract predatory birds, thereby enhancing the potential for biological pest control, particularly against rodents in oil palm plantations. We installed six artificial bird perches in a mature oil palm plantation in Keratong, Pahang, Peninsular Malaysia. Our data showed the presence of eight farmland bird species that utilised artificial perches, specifically White-throated Kingfisher, Collared Kingfisher, Oriental Magpie-Robin, Javan Myna, Barn Owl, Spotted Wood-Owl, Crested Serpent-Eagle, and Spotted Dove, and one forest associated species, Crested Goshawk. Our study is the first to describe predation of pest rodents by many of these eight farmland birds in oil palm plantations during daytime. Of the 1013 images taken, 48 showed rodent predation involving White-throated Kingfisher, Collared Kingfisher, Crested Serpent-Eagle, Crested Goshawk, Barn Owl and Spotted Wood-Owl. In a 24 h period, bird visits to artificial perches peaked between 10:00 am and 5:30 pm. Our findings suggest that artificial bird perches can facilitate the occurrence of diurnal and nocturnal predatory birds in oil palm plantations to control rodent infestation. The installation of artificial bird perches within oil palm plantations has the potential to enhance the ecosystem service of rodent biological control and increase avian biodiversity in palm oil producing countries.